MITOS IBU HAMIL DAN KEBUDAYAAN MASYARAKAT GUNUNG KIDUL (KAJIAN ANTROPOLINGUISTIK) - Latifah, Dinda Isni; Kurniasih, Cicih; Hendrawan, Sirat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study uses anthropolinguistics to investigate pregnancy myths in Javanese culture in the Gunung Kidul region. The community's strong conviction in a number of pregnancy-related myths and taboos that have been passed down through the generations is the driving force for this study. This study aims to characterize pregnancy myths and their cultural connotations. This study employed a qualitative approach using both primary and secondary data sources. In Gunung Kidul, informants with a native Javanese cultural background were interviewed to gather primary data, and literature research and document reviews were used to gather secondary data. The denotative, connotative, and mythical meanings that emerge in the community were revealed through descriptive data analysis approaches based on Roland Barthes' semiotic theory. The study's findings show that pregnancy myths in the Gunung Kidul community serve as a means of communicating moral principles, ethics, and ways to safeguard the mother and fetus in addition to acting as taboos or prohibitions. The connections between cultural, social, spiritual, and health facets of Javanese life are reflected in these myths. Furthermore, myths continue to persist as a type of indigenous knowledge that fortifies the community's social cohesion and cultural identity.